ODDS RATIO: A RESULT OF BUSINESS RESEARCH ANALYSIS - Karnowahadi - Karnowahadi (Admisi dan Bisnis, 2017)
ABSTRACTThe results of applied research in the field of good business deserve to be used as a material in the decision making process at the top level managers of a company (industry). The conclusion of a study should utilize and use the values resulting from the analysis of research data appropriately. Odds Ratio value is one of the values resulting from a research process and very meaningful in the conclusion. The Odds Ratio value reflects the comparative magnitude of a factor of exposure with the opposite factor. The value of research result as supporting of Odds Ratio is the value of p value and lower and upper odds ratio. Keyword : Odds Ratio; Business; Regression ABSTRAKHasil penelitian terapan bidang bisnis yang baik adalah hasil penelitian yang layak digunakan sebagai bahan pertimbangan dalam proses pengambilan keputusan pada manajer tingkat atas suatu perusahaan (industri). Pengambilan kesimpulan sebuah penelitian harus memanfaatkan dan menggunakan nilai-nilai yang dihasilkan dari analisis data penelitian secara tepat. Besaran nilai Odds Ratio merupakan salah satu nilai yang dihasilkan dari sebuah proses penelitian dan sangat berarti dalam pengambilan kesimpulan. Nilai Odds Ratio mencerminkan besaran pembanding antara sebuah faktor paparan dengan faktor kebalikannya. Besaran nilai hasil penelitian sebagai pendukung Odds Ratio adalah besaran nilai p value serta lower dan upper odds ratio. Kata kunci : Odds Ratio; Bisnis; Regresi